2009
DOI: 10.1073/pnas.0812436106
|View full text |Cite
|
Sign up to set email alerts
|

RNA repair restores hemoglobin expression in IVS2–654 thalassemic mice

Abstract: Repair of ␤-globin pre-mRNA rendered defective by a thalassemiacausing splicing mutation, IVS2-654, in intron 2 of the human ␤-globin gene was accomplished in vivo in a mouse model of IVS2-654 thalassemia. This was effected by a systemically delivered splice-switching oligonucleotide (SSO), a morpholino oligomer conjugated to an arginine-rich peptide. The SSO blocked the aberrant splice site in the targeted pre-mRNA and forced the splicing machinery to reselect existing correct splice sites. Repaired ␤-globin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 29 publications
1
67
0
Order By: Relevance
“…An effective way to eliminate this toxicity and expand therapeutic range of PPMO is to modify the transductive peptide. Moving toward a stable, versatile, robust, less toxic, inhibitor against T. gondii, our preliminary data demonstrate that the (RXR) 4 BX peptide as part of the ENR PPMO is effective and not toxic at 20 μM (Fig. S3).…”
Section: Knockdown Of Enr and Ap2xi3 Establishes That They Contribute Tomentioning
confidence: 99%
See 2 more Smart Citations
“…An effective way to eliminate this toxicity and expand therapeutic range of PPMO is to modify the transductive peptide. Moving toward a stable, versatile, robust, less toxic, inhibitor against T. gondii, our preliminary data demonstrate that the (RXR) 4 BX peptide as part of the ENR PPMO is effective and not toxic at 20 μM (Fig. S3).…”
Section: Knockdown Of Enr and Ap2xi3 Establishes That They Contribute Tomentioning
confidence: 99%
“…5B) demonstrated that ENR in plastids was robustly knocked-down by ENR-PPMO without adverse effect on YFP expression, but off-target PPMO did not abrogate ENR. Furthermore, (RXR) 4 BX peptide as part of ENR PPMO was effective and not toxic at 20 μM (Fig. S3).…”
Section: Knockdown Of Enr and Ap2xi3 Establishes That They Contribute Tomentioning
confidence: 99%
See 1 more Smart Citation
“…ASO have the potential to redirect a specific splicing event to prevent the production of a truncated or mutated protein, or to generate a specific protein isoform. Systemically delivered splice-switching ASO have been proven to be effective in vivo in animal models of b-thalassemia (26,27), spinal muscular atrophy (SMA; ref. 28,29), and Duchenne muscular dystrophy (30), and are currently tested in human clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…That this mechanism is feasible in vitro, in vivo in animals, and in patients has been demonstrated in numerous publications from this laboratory and by others. [3][4][5][6][7] The SSO mechanism of action is distinct from conventional antisense oligonucleotides (ASOs) and siRNAs that inhibit gene expression by degrading the target mRNA through RNase H and the RISC complex, respectively. Instead, SSOs sterically block sequences in pre-mRNA without leading to their degradation, thereby shifting the pattern of splicing.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%